Glycan-induced structural activation softens the human papillomavirus capsid for entry through reduction of intercapsomere flexibility - Yuzhen Feng; Dominik van Bodegraven; Alan Kádek; Ignacio L. B. Munguira; Laura Soria-Martinez; Sarah Nentwich; Sreedeepa Saha; Florian Chardon; Daniel Kavan; Charlotte Uetrecht; Mario Schelhaas; Wouter H. Roos (Nature Communications)
Abstract High-risk human papillomaviruses (HPVs) cause various cancers. While type-specific prophylactic vaccines are available, additional anti-viral strategies are highly desirable. Initial HPV cell entry involves receptor-switching induced by structural capsid modifications. These modifications are initiated by interactions with cellular heparan sulphates (HS), however, their molecular nature and functional consequences remain elusive. Combining virological assays with hydrogen/deuterium exchange mass spectrometry, and atomic force microscopy, we investigate the effect of capsid-HS binding and structural activation. We show how HS-induced structural activation requires a minimal HS-chain length and simultaneous engagement of several binding sites by a single HS molecule. This engagement introduces a pincer-like force that stabilizes the capsid in a conformation with extended capsomer linkers. It results in capsid enlargement and softening, thereby likely facilitating L1 proteolytic cleavage and subsequent L2-externalization, as needed for cell entry. Our data supports the further devising of prophylactic strategies against HPV infections.